Changes in Interventional Pain Physician Decision-Making, Practice Patterns, and Mental Health During the Early Phase of the SARS-CoV-2 Global Pandemic. Issue 12 (31st August 2020) - Joyce, Andrew A; Conger, Aaron; McCormick, Zachary L; Kendall, Richard W; Wagner, Graham; Teramoto, Masaru; Cushman, Daniel M
Abstract: Background and Objectives: The novel coronavirus outbreak (SARS-CoV-2) began in late 2019 and dramatically impacted health care systems. This study aimed to describe the impact of the early phase of the pandemic on physician decision-making, practice patterns, and mental health. Methods: An anonymous survey was distributed to physician members of the Spine Intervention Society (SIS) on March 24 and April 7, 2020. Respondents provided information regarding changes in clinical volume, treatment, and mental health (Patient Health Questionnaire [PHQ-4]) before April 10, 2020. Results: Of the 1, 430 individuals who opened the survey, 260 completed it (18.2%). Overall clinical and procedural volume decreased to 69.6% and 13.0% of prepandemic volume, respectively. Mean in-person clinic visits were reduced to 17.7% of total prepandemic clinic volume. Ongoing clinical visits were predominantly completed via telemedicine (video) or telephone (74.5%), rather than in-person (25.5%). Telemedicine and telephone visits represented 24.6% and 27.3% of prepandemic clinical volume, respectively. Respondents decreased in-person visits of select groups of high-risk patients by 85.8–94.6%. Significantly more providers reported increasing rather than decreasing prescriptions of the following medications: opioids (28.8% vs 6.2% of providers, P < 0.001), muscle relaxants (22.3% vs 5.4%, P < 0.001), neuropathic pain medications (29.6% vs 3.8%, P < 0.001), and acetaminophen (26.2% vs 4.2%, P < 0.001). Respondents' mean PHQ-4 score was 3.1, with 19% reporting moderate or severe psychological distress. Several demographic factors were significantly associated with practice changes. Conclusions: The novel coronavirus pandemic dramatically altered the practice and prescribing patterns of interventional pain physicians.